Unexpected enhanced catalytic performance via highly dense interfaces in ultra-fine amorphous-nanocrystalline biphasic structure. (December 2022) - Peng, Xinjie; Han, Jiuhui; Wang, Yutian; Bo, Zhenxing; Nie, Anmin; Li, Penghui; Li, Yanying; Wu, Haofei; Liu, Pan; Lu, Zhen; Bai, Haiyang
Highlights: Iron based metallic glasses with hyperfine spinodal decomposition morphology. Ultrahigh dense of amorphous/crystalline interfaces with the value of 2 × 10 16 m −2 . Admirable cycling degradation property and extraordinary dye degradation efficiency. Ultra-fine biphasic FeSiBNb films combine the advantages of high conductivity and abundant unsaturated coordination sites to strengthen the galvanic microcell effect, which significantly improves the catalytic performance. The hyperfine bicontinuous amorphous/crystalline composite FeSiBNb film designed by controllable deposition approach exhibits 300 times dye degradation efficiency than the commercial Fe powder without the assistance of hydrogen peroxide. Abstract: Metallic glasses (MGs) as effective catalysts have been extensively studied due to essentially disordered atomic configurations and widely adjustable micro-morphologies. The catalysis performance could be greatly promoted by introducing additional crystalline phases in the amorphous matrix due to the synergistic advantages of the crystalline and amorphous phases. However, the conventional casting and annealing approaches induced amorphous-crystalline (a/c) composites restrict the synergistic and galvanic cells effects because the generated crystalline phases are easily coarsened with meager a/c interfaces. Here, the artificial ultra-fine a/c Fe76 Si8 B13 Nb3 catalyst with spinodal decomposition morphology and extremely high dense a/c interfaces of 2 × 10 16 m −2 are achieved from MG film precursor with nanoscale phase separation by controllable surface diffusion during deposition and suppressive crystalline coarsening procedures. The designed ultra-fine a/c catalyst exhibits admirable cycling degradation property and extraordinary dye degradation efficiency of 300 times than that of the commercial Fe powder. Especially, the outstanding catalytic performances of a/c composite are achieved without the additional involvement of hydrogen peroxide assistance, which provides an environmental-friendly neutral catalytic condition and avoids the corrosive damage during commercial sewage-treatment. This work provides a distinct perspective to design and regulate catalytic performances by amorphous precursor with pre-existent ultra-fine structures. Graphical abstract: Image, graphical abstract